IMPLEMENTASI METODE DAKWAH ISLAM ALA NABI MUHAMMAD SAW DI INDONESIA - Asmaya, Enung (Fakultas Dakwah IAIN Purwokerto, 2014)
Da’wa methodology is an important aspect in Islamic missionary. It formulates, create, and determine the most relevant methods of da’wa in regards with the need of its audience (mad’u). It is necessary for da’wa to have a figure, actor, or agent who is really good at not only performing as an agent of da’wa but also functioning as a guide and consultant. The figure to be referred is Muhammad SAW, who was fully experienced with da’wawhen he lived in Makkah and Madinah. The characteristic of his da’wa was contextual, by which da’wa was implemented in respect to the prevalent social condition. This kind of methodology is the one that should be applied di Indonesia.